Performance and serum biochemical parameters of West African dwarf (WAD) goats fed unripe plantain peels as replacement for maize - Odeyinka, S.M.; Ayandiran, S.K. (Nigerian Journal of Animal Science, 2023)
In a sixteen-week trial, the performance and serum biochemical parameters of West African Dwarf (WAD) goats (5-7 months old) fed unripe plantain peels (UPP) as a replacement for maize were evaluated. The animals were randomly allotted to five treatments in a completely randomized design. Five concentrate diets were compounded with the inclusion of UPP at 0, 25, 50, 75 and 100% levels respectively. The diets were fed to the animals at 3% of their body weights. The results showed that proximate and fibre fractions of the concentrate diets increased with increase in the inclusion of UPP. The daily gain of 0%UPP was significantly higher (p<0.05) compared to other diets. The crude protein and crude fibre digestibility of animals fed diets 25%, 50%, 75% and 100%UPP were significantly higher (P<0.05) than 0%UPP.The total cholesterol (mg/dl) levels of the animals fed diets 25% up to 100%UPPwere significant lower (p<0.05) than 0%UPP diet. It could be concluded that UPP as substitute for maize improved performances and had no deleterious effect on serum biochemical parameters of WAD goats.